Comparative Analysis Method of Work, Time and Cost of Concrete Spun Pile Work with Bored Pile On Construction of the Light Rail Transit (LRT) - Yopi Lutfiansyah; Muhammad Akhsan (Journal of Applied Science, Engineering, Technology, and Education, 2019)
Building construction consists of two parts, namely the upper building and lower building. The upper building transmits forces to the lower building, which then from the lower building is channeled to the supporting soil. Pile foundation is a part of the lower structure that is used to receive and distribute the load from the upper structure to the supporting soil which is located at a certain depth determined by the results of the soil investigation. Piles are used as building foundations if the soil under the building base does not have enough bearing capacity to carry the weight of the building working on it. The stake used in this comparison is the Concrete Spun Pile and Bored Pile foundation. The results of the study show that the Bored pile method is slightly more complicated than the Concrete spun pile method. In terms of time required for the Concrete spun work is 6 hours, while for Bored piles per point is 9 hours assuming the work is 3 months In terms of the cost of foundation work of 1000mm diameter and 30m depth using the Concrete spun pile method is Rp. 13,704,241,634.10 for 156 points. whereas for the Bored pile method with a diameter of 1200mm and a depth of 30m is Rp. 14,242,797,932.85 for 78 points. So the foundation work with the Concrete spun pile method is more effective and efficient than the Bored pile method based on the method of implementation, time and cost.